2023
DOI: 10.1111/1750-3841.16473
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial characteristics of ethyl acetate polar fractions from walnut green husk

Abstract: Walnut green husk (WGH) is rich in natural compounds and is valued as a potential source of antioxidant and antimicrobial properties. In this study, the antioxidant and antimicrobial activities of petroleum ether polar fraction, dichloromethane polar fraction, ethyl acetate polar fraction (EAPF), and nbutanol polar fraction from WGH were analyzed. The results showed that EAPF exhibited the highest total flavonoid content (65.74 ± 1.01 mg rutin equivalents [RE]/g dry weight [DW]) and total phenol content (48.73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Additionally, variations in bacterial size were observed, with some demonstrating dissolution. Comparable findings have been previously reported in antibacterial assessments involving other WGH extracts [11]. Vanillic acid, chlorogenic acid, and cinnamaldehyde, which were found in WGHa, are responsible for these morphological and structural alterations in the cell membranes of the selected bacteria.…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 84%
See 3 more Smart Citations
“…Additionally, variations in bacterial size were observed, with some demonstrating dissolution. Comparable findings have been previously reported in antibacterial assessments involving other WGH extracts [11]. Vanillic acid, chlorogenic acid, and cinnamaldehyde, which were found in WGHa, are responsible for these morphological and structural alterations in the cell membranes of the selected bacteria.…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 84%
“…No antimicrobial activity was observed for WGHb and WGHc at concentrations of 100 mg/mL or lower. A previous study found that the MIC for the ethyl acetate fraction of a WGH extract against both E. coli and B. cereus was 31.25 mg/mL [11]. However, a combination of an n-hexane extract and a 80% hydroethanol extract of WGH exhibited MIC values of 2, 1, 0.5, and 4 mg/mL against S. aureus, B. subtilis, E. coli, and P. aeruginosa, respectively [10].…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 96%
See 2 more Smart Citations
“…Numerous studies have shown that compounds extracted from plants, animals, and microorganisms have antibacterial activity and are expected to be novel antibacterial agents. Extensive experiments have demonstrated the antibacterial effects of walnut extract [ 69 , 70 , 71 , 72 , 73 ]. In fact, EeDJF has promising antibacterial activity.…”
Section: Extractsmentioning
confidence: 99%